2021
DOI: 10.1021/acs.jcim.1c01109
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Workflow for Modeling Ligand Complexes of Zinc Metalloproteins

Abstract: Zinc metalloproteins are ubiquitous, with protein zinc centers of structural and functional importance, involved in interactions with ligands and substrates and often of pharmacological interest. Biomolecular simulations are increasingly prominent in investigations of protein structure, dynamics, ligand interactions, and catalysis, but zinc poses a particular challenge, in part because of its versatile, flexible coordination. A computational workflow generating reliable models of ligand complexes of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 73 publications
(107 reference statements)
0
15
0
Order By: Relevance
“…The B3LYP hybrid functional , with the 6-31+G** basis set plus the D3 dispersion correction (B3LYP-D3/6-31+G**/C36) were employed as the high-level QM counterpart to refine the single-point energies along the optimized MEPs. We note that the combination of the levels of theory (DFTB3 and B3LYP-D3) has been proposed previously for enzyme catalysis simulations. , It has also been demonstrated that both the DFTB3 and B3LYP methods are applicable for studying concerted reaction steps in QM/MM simulations. , …”
Section: Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…The B3LYP hybrid functional , with the 6-31+G** basis set plus the D3 dispersion correction (B3LYP-D3/6-31+G**/C36) were employed as the high-level QM counterpart to refine the single-point energies along the optimized MEPs. We note that the combination of the levels of theory (DFTB3 and B3LYP-D3) has been proposed previously for enzyme catalysis simulations. , It has also been demonstrated that both the DFTB3 and B3LYP methods are applicable for studying concerted reaction steps in QM/MM simulations. , …”
Section: Methodsmentioning
confidence: 83%
“…We note that the combination of the levels of theory (DFTB3 and B3LYP-D3) has been proposed previously for enzyme catalysis simulations. 66 , 67 It has also been demonstrated that both the DFTB3 and B3LYP methods are applicable for studying concerted reaction steps in QM/MM simulations. 68 , 69 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, transition organometallic probes possess the following characteristics: (1) highly luminous efficiency, long lifetime and high stability; (2) large Stokes shift of excitation and emission, and easy regulation of excitation and emission wavelengths; and (3) low cell imaging incubation concentration and less interference of normal cell activity. 26,27 Meanwhile, because of their low price and nontoxicity, easy functional modification and synthesis, photochemical stability, and desirable photophysical properties, [28][29][30][31][32][33][34][35][36][37] zinc complexes are widely used as excellent luminescent materials.…”
Section: Introductionmentioning
confidence: 99%
“…2,15 In fact, the latest parametrization of the Rosetta energy function (ref2015) 16 did not refit the parameters for the metal ions which originally are from CHARMM27 with empirically derived Lazaridis-Karplus solvation terms. To adequately treat metal sites in proteins quantum mechanical treatments such as in hybrid quantum mechanics/molecular mechanics (QM/MM) simulations 17,18 is needed whose computational cost is prohibitive for regular protein design tasks. QM/MM simulations can however be used to verify coordination chemistry for select candidate proteins.…”
Section: Introductionmentioning
confidence: 99%